Environmental and climate finance in a new world: How past environmental aid allocation impacts future climate aid - Christopher Marcoux; Bradley C. Parks; Christian M. Peratsakis; J. Timmons Roberts; Michael J. Tierney (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2013)
In this paper we update previous work that categorizes foreign aid projects in terms of their likely impact on the natural environment. We then document trends in the global distribution of environmental aid over time and show that environmental aid has increasingly focussed on global environmental issues (especially climate change), rather than local issues in recipient countries. Somewhat surprisingly, we also find that environmental aid is increasingly allocated through bilateral aid agencies rather than through the increasing number of multilateral channels created for this purpose. After providing these descriptive statistics and demonstrating trends, we offer a tentative explanation for this puzzling pattern. We argue that each individual aid project represents a negotiation between donor and recipient. This additional level of bargaining significantly conditions the costs and benefits of multilateralism for donors, especially as recipients have multiple outside options for obtaining development finance. Reflecting the growing political salience of global environmental threats, donors are providing increasing levels of environmental aid, and especially climate finance. However, at the same time, donors are increasingly failing to co-ordinate their allocation of climate finance (and other environmental aid) within multilateral institutions. At a practical level, this raises the question whether the effect of increasing levels of funding will be undercut by decreasing co-ordination and efficiency.
Keywords: F35; F64; Q54; Q56; 330; development finance; environmental aid; climate policy